Identification and quantification of flavonoids in yellow grain mutant of rice (Oryza sativa L.). (15th February 2018) - Kim, Backki; Woo, Sunmin; Kim, Mi-Jung; Kwon, Soon-Wook; Lee, Joohyun; Sung, Sang Hyun; Koh, Hee-Jong
Highlights: High level of flavonoids containing rice mutant is reported for the first time. 19 flavonoids were identified or tentatively identified in a yellow grain mutant by UHPLC-DAD-ESI-Q-TOF-MS. Isoorientin was particularly abundant in embryo tissue. Yellow grain mutant showed the high phenolic content and antioxidant activity. Abstract: Flavonoids are naturally occurring phenolic compounds with potential health-promoting activities. Although anthocyanins and phenolic acids in coloured rice have been investigated, few studies have focused on flavonoids. Herein, we analysed flavonoids in a yellow grain rice mutant using UHPLC-DAD-ESI-Q-TOF-MS, and identified 19 flavonoids by comparing retention times and accurate mass measurements. Among them, six flavonoids, isoorientin, isoorientin 2″- O -glucoside, vitexin 2″- O -glucoside, isovitexin, isoscoparin 2″- O -glucoside and isoscoparin, were isolated and fully identified from the yellow grain rice mutant, and the levels were significantly higher than wild-type, with isoorientin particularly abundant in mutant embryo. Significant differences in total phenolic compounds and antioxidant activity were observed in mutant rice by DPPH, FRAP and TEAC assays. The results suggest that the representative six flavonoids may play an important role in colouration and antioxidant activity of embryo and endosperm tissue. The findings provide insight into flavonoid biosynthesis and the possibility of improving functionality in rice.